Improving the Quality of Tutorials to Create a Quality Culture Through an Integrative Selection of Tutors - Titik Setyowati; Rahyu Setiani; Dwi Sambada; Wuwuh A. Surasmi; Dwikoranto (Indonesia Approach Education, 2020)
Open University is needed to meet the needs of studying without being limited by space, time, amount, cost, age, and distance with a quality tutor. This study aims to describe the ideal form of tutor recruitment, the role of tutors and get quality tutors. This survey research was conducted at the Distance Learning Program Unit (DLPU) Surabaya with data collection methods through observation, interviews, questionnaires and documentation. Sources of data were obtained from Study groups, Tutors, Department of Education, Regional Responsibility in the tutorial period 2019.1 and 2019.2. Data were analyzed descriptively. The results showed that: (1) The ideal form of tutor recruitment is through tutor selection, through the tutor candidate test, through agency recommendations and special offers. (2) The role of tutors in the professional learning process is that tutors are still needed for certain subjects, as innovators and motivators, to play a role in reducing dropout. (3) To get quality tutors and not only as a part-time job so that tutors in working remain professional is to build a sound system. The obligations and rewards that are received appropriately. Between taxes and a decent income. Also, between expertise or rank need to be adjusted to the level of compensation which is given.